PENGARUH KEBIJAKAN UTANG, LIKUDITAS, INTENSITAS PERSEDIAAN TERHADAP AGRESIVITAS PAJAK - Laras Pangesti; Endang Masitoh W; Anita Wijayanti (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2020)
This study aims to determine the effect of Debt Policy, Liquidity, Inventory Intensity on Tax Aggressiveness. With secondary data from the financial statements of mining sector companies listed on the Stock Exchange in 2016-2018, using 40 respondents and purposive sampling methods, namely (1) Manufacturing Companies that have been listed on the Indonesia Stock Exchange that have submitted financial reports as of 31 December according to the study period. (2) Companies that submit complete data. (3) Using the Dollar in its financial reporting. (4) Has an ETR value between 0-1. (5) Companies that have never suffered losses during the study period. The analysis technique uses multiple linear regression with SPSS version 18. The results of this study indicate (1) Debt Policy has an effect and significant effect on tax aggressiveness, (2) Liquidity has no effect on tax aggressiveness, 2) Inventory intensity has no effect on tax aggressiveness. Benefits of research, (1) For practitioners, input for investors in investing in the capital market is also a reference to make a healthy company with this research. (2) For Theoretical, Add insight into Debt Policy, Liquidity, Inventory Intensity and Tax Aggressiveness.